Influence of Instagram Content Marketing and e-wom on Consumer Purchase Decisions Through Buying Interest (Study on Ayucitra Gallery Consumers By Monokrom Jombang) - Nurul Lailiyah; Yuslinda Handini; Ika Sisbintari; Shanshan Xu; Murphy Xavier; McCarty Elliot (Journal Markcount Finance, 2024)
Social media is a tool for searching and selecting information in the form of products and services. The use of social media in Indonesia continues to grow every year, therefore it is widely used by marketers as an opportunity to introduce and offer products. One of them is by creating content marketing and e-WOM. Content marketing and e-WOM are strategies that are considered quite effective in marketing and introducing products to consumers. The purpose of this study was to determine the impact of Instagram content marketing and e-WOM on consumer purchasing decisions through the purchase interest variable. The population in the study were consumers of the Ayucitra gallery by monochrome jombang, with a sampling technique using purposive sampling of 120 respondents. Data analysis using path analysis with SEM (Structural Equation Modeling) using smartPLS.3.0 software. The findings concluded that content marketing (X1) has a positive and significant effect on consumer buying interest (Z), e-WOM (X2) has a positive and significant effect on consumer buying interest (Z), buying interest has a positive and significant effect on consumer purchasing decisions (Y), content marketing (X1) has a positive and significant effect on consumer purchasing decisions (Y), e-WOM (X2) has a positive and significant effect on consumer purchasing decisions (Y). content marketing (X1) has a positive and significant effect on consumer purchasing decisions mediated by consumer buying interest (Z) at Ayucitra by Monochrome gallery, e-WOM (X1) has a positive and significant effect on consumer purchasing decisions mediated by consumer buying interest (Z) at Ayucitra by Monochrome gallery